2016
DOI: 10.1155/2016/2517514
|View full text |Cite
|
Sign up to set email alerts
|

Human Umbilical Cord Mesenchymal Stem Cells Therapy in Cyclophosphamide-Induced Premature Ovarian Failure Rat Model

Abstract: Premature ovarian failure (POF) is one of the most common causes of infertility in women. In our present study, we established cyclophosphamide- (CTX-) induced POF rat model and elucidated its effect on ovarian function. We detected the serum estrogen, follicle stimulating hormone, and anti-Müllerian hormone of mice models by ELISA and evaluated their folliculogenesis by histopathology examination. Our study revealed that CTX administration could severely disturb hormone secretion and influence folliculogenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
90
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(107 citation statements)
references
References 45 publications
12
90
1
4
Order By: Relevance
“…These results are in line with the results of other previous studies (Liu et al, 2014;Sheikhansari, Aghebati-Maleki, Nouri, Jadidi-Niaragh, & Yousefi, 2018;Song et al, 2016;Sun et al, 2013;Woods et al, 2013;Xiao et al, 2016).…”
Section: Previous Mice Model Studies Have Shown That Busulfan Targetssupporting
confidence: 93%
See 1 more Smart Citation
“…These results are in line with the results of other previous studies (Liu et al, 2014;Sheikhansari, Aghebati-Maleki, Nouri, Jadidi-Niaragh, & Yousefi, 2018;Song et al, 2016;Sun et al, 2013;Woods et al, 2013;Xiao et al, 2016).…”
Section: Previous Mice Model Studies Have Shown That Busulfan Targetssupporting
confidence: 93%
“…In recent years, the use of MSCs as cell therapy for the treatment of POF has been investigated in many studies. MSCs from various sources have been used for this purpose, and it has been found that these cells have different abilities in improving ovarian function (Fu, He, Xie, & Liu, ; Song et al, ; Sun et al, ; Xiao et al, ). In a previous study, a successful treatment of POF mice using MSC transplantation was reported (Lai et al, ; Liu et al, ; Wang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…This experiment reported that the ratio of tubal factor infertility in women over 35 years old is significantly higher than it is in women under 30 years old. Second, chemotherapy damages the function of the ovary mainly because it can induce the apoptosis of granulosa cells, it can damage the ovarian microenvironment, and it can injure growing follicles (Roness, et al 2014;Song, et al 2016). Chemotherapy also damaged the morphology of fallopian tubes, as shown in our study.…”
Section: Discussionsupporting
confidence: 60%
“…Recently, Song and colleagues transplanted human UC‐MSCs derived from a male baby and successfully tracked them in ovaries by fluorescence in situ hybridization using the Y chromosome as a marker. UC‐MSCs restored the hormone balance, stimulated folliculogenesis, and reduced ovarian cell apoptosis (Song et al ., ). MSC‐derived oogenesis did not result in fully functional follicles, but bone marrow infusions in mice helped to postpone age‐related reproductive failures and also improved offspring survival (Selesniemi et al ., ).…”
Section: Mesenchymal Stem Cell Transplantationmentioning
confidence: 97%